Jenis-Jenis Kurikulum Pendidikan Agama Islam (Telaah Tentang Written Curriculum And Hidden Curriculum) - Mulyadi, Mulyadi; Inayati, Mahfida; Maimun, Maimun (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
The curriculum is a series of educational activities in the form of programs and schedules of educational activities that are systematically designed. The aim of the Islamic religious education curriculum is to facilitate the learning process in schools, both elementary schools and universities, which is a plan to support the teaching and learning process so that it can become effective learning which consists of a lot of learning material, both general learning and Islamic religious education learning. So it is necessary to know in depth about the types of curriculum which focus on written curriculum and hidden curriculum. A written curriculum is a plan or program that is written in detail and systematically, while a hidden curriculum can also be interpreted as a form of curriculum that is not included in an official plan or program.